CLINICAL EFFECTIVENESS OF AMBULATORY HYSTEROSCOPIC POLYPECTOMY USING SMALL DIAMETER HYSTEROSCOPE AND PULSED DIODE LASER IN MENOPAUSAL PATIENTS - Сафронов, Олег Владимирович; Казачкова, Элла Алексеевна; Казачков, Евгений Леонидович; Сафронова, Ирина Владимировна; Мшак-Манукян, Гоар Норайровна; Шалонина, Татьяна Германовна (Mother and Baby in Kuzbass, 2023)
Endometrial polyps have leading positions in the structure of intrauterine and gynecological pathology. Development of minimally invasive, effective and safe techniques of their removal is of utmost importance.The aim of the research – еvaluation of clinical effectiveness of ambulatory hysteroscopic polypectomy using a small diameter hysteroscope and a diode laser in a pulsed mode.Materials and methods. A retrospective comparative study of the outcomes of ambulatory hysteroscopic polypectomy was performed in 80 postmenopausal patients with histologically verified endometrial polyps. The 1st group comprised 48 women who underwent polypectomy using small diameter hysteroscope and pulsed diode laser. The 2nd group consisted of 32 patients who underwent surgeries using small diameter hysteroscope and semirigid bipolar angled mini electrode.Results. The method of ambulatory hysteroscopic polypectomy using small diameter hysteroscope and pulsed diode laser allows removing endometrial polyps in the postmenopause in 100 % of the patients. The use of a small diameter hysteroscope makes it possible to perform surgery without cervical canal dilation, reduce the amount of uterus distension fluid, shorten operative time (to 19.54 ± 2.09 minutes).Conclusion. The proposed method of polypectomy demonstrated high clinical effectiveness and safety. This method could be used to treat postmenopausal patients in ambulatory settings.
Keywords: endometrial polyps; hysteroscopic polypectomy; diode laser